Mitochondrial Bioenergetics and Fiber Type Assessments in Microbiopsy vs. Bergstrom Percutaneous Sampling of Human Skeletal Muscle - Hughes, Meghan C.; Ramos, Sofhia V.; Turnbull, Patrick C.; Nejatbakhsh, Ali; Baechler, Brittany L.; Tahmasebi, Houman; Laham, Robert; Gurd, Brendon J.; Quadrilatero, Joe; Kane, Daniel A.; Perry, Christopher G. R. (Frontiers in Physiology, 2015)
Microbiopsies of human skeletal muscle are increasingly adopted by physiologists for a variety of experimental assays given the reduced invasiveness of this procedure compared to the classic Bergstrom percutaneous biopsy technique. However, a recent report demonstrated lower mitochondrial respiration in saponin-permeabilized muscle fibre bundles (PmFB) prepared from microbiopsies vs Bergstrom biopsies. We hypothesized that ADP-induced contraction (rigor) of smaller length microbiopsy PmFB causes a greater reduction in maximal respiration vs Bergstrom, such that respiration could be increased by a myosin II ATPase-inhibitor (Blebbistatin; BLEB). 11 males and females each received a 2 mm diameter percutaneous microbiopsy and a 5 mm diameter Bergstrom percutaneous biopsy in opposite legs. Glutamate/malate (5 mM/0.5 mM) - supported respiration in microbiopsy PmFB was lower than Bergstrom at submaximal concentrations of ADP. 5 μM BLEB reduced this impairment such that there were no differences relative to Bergstrom +/- BLEB. Surprisingly, pyruvate (5 mM)-supported respiration was not different between either biopsy technique +/- BLEB, whereas BLEB increased succinate-supported respiration in Bergstrom only. H2O2 emission was lower in microbiopsy PmFB compared to Bergstrom PmFB in the presence of BLEB. Microbiopsies contained fewer type I fibres (37% vs 47%) and more type IIX fibres (20% vs 8%) compared to Bergstrom possibly due to sampling site depth and/or longitudinal location. These findings suggest that smaller diameter percutaneous biopsies yield lower glutamate-supported mitochondrial respiratory kinetics which is increased by preventing ADP-induced rigor with myosin inhibition. Microbiopsies of human skeletal muscle can be utilized for assessing mitochondrial respiratory kinetics in PmFB when assay conditions are supplemented with BLEB, but fibre type differences with this method should be considered.